Challenges in the design of a customized location-based mobile learning application - Lliteras, Alejandra Beatriz
This paper presents an analysis of the challenges present in the design of a location-based mobile learning application. The analysis was performed on a customization of the application "Resuelvo Explorando" for the thematic of "Healthy Eating". Considering the relevance of usability in this type of applications, a usability analysis is presented using a heuristic method. With this work, we expect to contribute in the discussion regarding good practices to address the challenges present in this type of applications from the design stage.